Rural Development Research Trends: Bibliometric Analysis Using Publish or Perish and Vosviewer - Komang Ariyanto (CV. Media Digital Publikasi Indonesia, 2023)
This article aims to revisit the study of rural development, agricultural development, and rural livelihoods by highlighting publications in Google Scholar and Semantic Scholar from 1980 to 2023. The study utilized Google Scholar's and Semantic Scholar's 43-year citation database to compile articles. The keywords used in this study were